Odpowiedzi

2010-03-24T00:25:14+01:00
3 + 7 + 11 = (3 * 7 * 11) / 11
21 = 21
L = P

Szukane liczby pierwsze to: 3; 7 i 11.
2010-03-24T00:25:17+01:00
X , y, z - szukane liczby pierwsze
Mamy
11*( x + y + z) = x*y*z
Niech x < y < z
x*y*z /(x+y+z) = 11
Niech z = 11
x*y*11/ (x+y+11) = 11 skracam przez 11
x*y /(x+y + 11) = 1
czyli
x*y = x +y + 11
x*y - y = 11 + x
(x - 1)*y = 11 + x
Niech
x = 2 , wtedy (2-1)*y = y = 11+2 = 13 > 11
sprzeczność z założeniem
Niech
x = 3, wtedy (3-1)*y = 2y = 11+3 = 14
2y = 14
y = 7 < 11
spr. L = 11*( 3+7 +11) = 11*21 = 231
P = 3*7*11 = 21*11 = 231
L = P
x = 7 , wtedy (7-1)y = 6y = 11 + 7 = 18
6y = 18
y = 3 , ale 7 > 3 ( x > y ) - sprzeczność z założeniem
Odp. 3,7,11